Thoracic spine dislocation in Gorham–Stout Syndrome: Case report and literature review - Jaccard, Alexandre (Surg Neurol Int, 2018)
BACKGROUND: The Gorham–Stout syndrome (GSS), also known as phantom bone disease, is a rare bone condition of unknown etiology. Involvement of the spine is described in <50 cases in the literature. Here, we report a case of thoracic spine fracture dislocation in a young female who was known to have GSS. CASE DESCRIPTION: A 23-year-old female developed a left spontaneous hemothorax 10 years previously along with left ribs lytic lessions. Pleural and rib biopsies diagnosed angiomatosis and the clinical diagnosis of GSS was established. Following a minor trauma, she presented with a Frankel B deficit attributed to a T3-T4 fracture dislocation with severe spinal cord compression. The patient underwent halo traction with CT. Following reduction, decompression and C5 to T8 with instrumented fusion (posterior only), she neurologically improved to Frankel D, 2 years postoperatively. CONCLUSION: Although GSS is a rare condition in the spine, it may lead to gross instability and catastrophic vertebral fracture/dislocation with paraparesis. Acute spinal cord decompression with stabilization may be warranted to achieve neurological improvement.